Do tissue spears used to clear ear canal pus improve hearing? A case series study of hearing in remote Australian Aboriginal children with chronic suppurative otitis media before and after dry mopping with tissue spears. (21st December 2015) - Sparrow, K; Sanchez, L; Turner, D; MacFarlane, P; Carney, A S
Abstract: Objective: To determine whether the use of tissue spears to remove otorrhoea from Aboriginal children's ear canals improves hearing in the affected ear. Design: Case series study with controls. Methods: The study comprised 61 Aboriginal children from communities in the remote arid zone of South Australia who had otorrhoea obscuring the tympanic membrane in 1 or both ears. Eighty ears were treated with tissue spears, and hearing was assessed before and after treatment. Results: Forty-two children had unilateral and 19 had bilateral active disease. An additional 13 ears without otorrhoea served as controls. Improvement by 5 dB HL or greater in a four-frequency pure tone average occurred in 41.3 per cent of treated ears. Subsequently, blinded audiologists made qualitative judgements that a functional improvement in hearing had occurred after tissue spear use in 28.4 per cent of ears. Conclusion: Tissue spears can improve hearing thresholds in a significant proportion of children with otorrhoea. However, the duration of the effect is unknown.